Endoscopic ultrasound guided hepatic interventions. Issue 1 (17th April 2020) - Hashimoto, Rintaro; Chang, Kenneth J.
Abstract : Intervention for liver disease has predominantly been performed through the percutaneous approach. However, as endoscopic ultrasound (EUS) applications have expanded, there have emerged various EUS‐guided interventions for liver disease, a space we call "Endo‐Hepatology". EUS‐guided liver biopsy can be considered the "forerunner" of Endo‐Hepatology and has become a clinical option for patients requiring histologic diagnosis and staging of their liver disease. EUS also enables direct access to the portal vein. Subsequently, many procedures are being explored, such as angiography, measurement of the portosystemic pressure gradient, portal vein sampling to detect cancer cell or DNA, and EUS‐guided transhepatic intrahepatic portosystemic shunt creation. Since the transducer is close to the liver, especially the left and caudate lobes, EUS can be used as a rescue when the percutaneous approach is not favorable and EUS‐guided treatments of liver tumor, cyst and abscess have been reported. This review summarizes the available studies of EUS‐guided intervention in the liver.